2019
DOI: 10.1016/j.jhealeco.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Seeing and hearing: The impacts of New York City’s universal pre-kindergarten program on the health of low-income children

Abstract: Prior research suggests that high quality universal pre-kindergarten (UPK) programs can generate lifetime benefits, but the mechanisms generating these effects are not well-understood. In 2014, New York City made all 4-year-old children eligible for high-quality UPK programs that emphasized developmental screening. We examine the effect of this program on the health and healthcare utilization of children enrolled in Medicaid using a difference-in-regression discontinuity design that exploits both the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(37 reference statements)
1
6
2
Order By: Relevance
“…First, we analyzed hearing problems (i.e., starting from “38” in ICD 9 code) and vision problems (i.e., starting from “36” and “37” in ICD-9 codes) as outcomes using the same analytical model (see Appendix D ). These outcomes may have a positive association with Pre-K attendance as shown in a previous study [ 15 ]. Second, we constructed three study subsamples based on the participants’ continuity of Medicaid enrollment because not all participants remained enrolled in Medicaid throughout the study period (i.e., from the beginning of 2011 to the end of 2017).…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…First, we analyzed hearing problems (i.e., starting from “38” in ICD 9 code) and vision problems (i.e., starting from “36” and “37” in ICD-9 codes) as outcomes using the same analytical model (see Appendix D ). These outcomes may have a positive association with Pre-K attendance as shown in a previous study [ 15 ]. Second, we constructed three study subsamples based on the participants’ continuity of Medicaid enrollment because not all participants remained enrolled in Medicaid throughout the study period (i.e., from the beginning of 2011 to the end of 2017).…”
Section: Methodsmentioning
confidence: 55%
“…However, few studies to date have empirically addressed the short-term effects of Pre-K programs on childhood health outcomes. A recent national heart study revealed that attending a universal Pre-K program in New York City was associated with increased diagnosis of several health problems (e.g., asthma, vision problems, and hearing problems) Similarly, an increased use of healthcare services (e.g., treatment for hearing or vision problems) was observed [ 15 ]. These findings suggest Pre-K programs may offer valuable settings for the early detection of children’s ill health status in children and promote the use of appropriate health care services.…”
Section: Introductionmentioning
confidence: 99%
“… 73–75 Hiring school nurses to help students navigate from screening to full eye exams and comply with treatment was reported to be effective compared with screening alone 76 (although some universal childhood screening programmes were very effective at promoting follow-up). 77 …”
Section: Resultsmentioning
confidence: 99%
“…[73][74][75] Hiring school nurses to help students navigate from screening to full eye exams and comply with treatment was reported to be effective compared with screening alone 76 (although some universal childhood screening programmes were very effective at promoting follow-up). 77 Initiatives with wider, integrated approaches also demonstrated effectiveness at improving attendance at follow-up eye exams (though not always significantly so). These initiatives tended to include several components, such as prescheduling follow-up appointments, 43 78 running follow-up appointments at convenient locations, 79 incorporating education elements 43 59 80 and providing financial incentives.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…The few studies that assess the effects of daycare exposure on child health are inconclusive in terms of the direction and magnitude of the effects. Programs targeting families from low socio-economic backgrounds generally benefit children's health (e.g., Conti et al, 2016, Hong et al, 2019 while the effects of universal daycare programs on health depend on the quality of the program, the counterfactual care mode, the considered age groups and the outcomes at measure. For example, a cheap, low-quality daycare expansion in Quebec has adverse health effects (e.g., Baker et al, 2008, Heckman et al, 2010, Kottelenberg and Lehrer, 2013, while daycare expansions providing better quality care have the potential to have null or positive effects on child health (e.g., Bosque-Mercader, 2022, Cornelissen et al, 2018, van den Berg and Siflinger, 2022.…”
Section: Introductionmentioning
confidence: 99%